The toxicity of 3-monochloro-1, 2-propanediol (+) to activated T cells in mice. Issue 4 (4th July 2017) - Guan, Shuang; Yu, Xin; Fang, Baochen; Huang, Yixuan; Xu, Linli; Lu, Jing
ABSTRACT: 3-monochloro-1, 2-propanediol (3-MCPD) is a member of a group of chemicals known as chloropropanols that has been detected in a wide range of foods. In the present study, we found that its α-chlorohydrin structure (3-MCPD(+)) has toxic effects on activated T cells in mice. Specifically, the data showed that 1, 2, and 4 mM 3-MCPD(+) markedly inhibited ConA-induced T cell proliferation and Th1/Th2 cytokine production. Furthermore, Western blotting was used to study the mechanism of action of 3-MCPD(+). The data revealed that 3-MCPD(+) inhibited the activation of the Ca 2+ /CaM/I-κB-NF-κB and Ca 2+ /CaM/CaN/NFAT signaling pathways. In vivo, 3-MCPD(+) treatment significantly inhibited 2, 4-dinitrofluorobenzene-induced delayed-type hypersensitivity reactions in mice. These observations indicated that 3-MCPD(+) is toxic to activated mouse T cells in vitro and in vivo.